Nanomaterials Applied to Fuel Cells and Catalysts - András Tompos (Nanomaterials)
Hydrogen and fuel cell technologies are accepted by consensus as being part of the future energy system, especially in hard-to-abate segments where electrification is not an efficient solution [...]